Does obesity modify the relationship between physical activity and breast cancer risk? - Neil-Sztramko, S.; Boyle, Terry; Milosevic, E.; Nugent, S.; Gotay, C.; Campbell, K. (Springer, 2017)
Purpose: With only 5–10% of breast cancer cases attributed to genetic inheritance, prevention efforts have focused on modifiable risk factors. Physical activity plays a role in reducing breast cancer risk; however, the interaction between physical activity and other modifiable risk factors, such as obesity, has received little attention. Methods: A systematic review and meta-analysis was conducted of studies examining the relationship between physical activity and breast cancer and how it may be modified by body mass index (BMI). Results: A total of 29 papers were included: 18 were cohort and 11 were case–control studies. Overall, a significant reduction in the relative risk of breast cancer was found in postmenopausal women with high versus low levels of physical activity for women with a BMI < 25 kg/m 2 (RR 0.85, 95% CI 0.79, 0.92) and =25 kg/m 2 (RR 0.87, 95% CI 0.81, 0.93) but not =30 kg/m 2 (RR: 0.93, 95% CI 0.76, 1.13). Physical activity was not associated with a significant reduction in risk of breast cancer in premenopausal women in any BMI group. Conclusion: The results of this meta-analysis suggest that physical activity is associated with a larger breast cancer risk reduction among women who are normal weight or overweight than among women who are obese. Since the included studies used diverse methods for assessment of physical activity and categories of BMI, results should be interpreted with caution and additional work is needed.